Differentiation of Lard from Other Edible Fats by Gas Chromatography-Flame Ionisation Detector (GC-FID) and Chemometrics - Dahimi, Omar; Hassan, Mohd. Sukri; Rahim, Alina Abdul; Abdulkarim, Sabo Mohammed; Mashitoh A., Siti (Journal of Food and Pharmaceutical Sciences, 2014)
The presence of lard or its derivatives in any food products is a serious religious issue among Muslim and Judaism. Thus, the objective of this study was to investigate the use of gas chromatography with flame ionisation detector (GC-FID) coupled with chemometrics techniques such as Principle Components Analysis (PCA) and K-mean cluster analysis to differentiate lard adulteration at very low concentrations in beef and chicken fats. The measurements were made from the pure lard, beef tallow, pure chicken fat; and beef tallow (BT), chicken fat (CF) adulterated with different concentrations of lard (0.5%-10% in BT and CF). The data were first scaled into standardisation before PCA is performed to each of the scaled data using Unscrambler software. The Scores plots and loadings plots of each scaled data were compared and studied. The results showed that lard contains higher fatty acid (FA) of C18: 2cis and low C16:0 FA, but oppositely for beef tallow and chicken fat. The amount of C4:0, C14:0, and C18:0 FAs are approximately similar for all fats.Â  Others FAs are small in amount and nearly similar for both. Additionally, PCA was able to significantly identify lard, beef fat, chicken fat and the mixtures of lard and beef tallow, lard and chicken fat, even at lower concentration level (0.5 % lard-99.5% beef tallow / chicken fat (w/w). K-mean cluster only able to classify the pure lard (LD), pure chicken fat (CF) and pure beef tallow (BT)